FACTORS IMPACTING EMPLOYEE RETENTION: A CASE OF PRIVATE COMPANIES IN SAUDI ARABIA - Reem Hashem Al-Gharbi; Uzma Javed (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The study aimed to determined factors which impact retention from employee perspective and retention practices used by the employers for retained values of employees. The study was conducted in private companies in three cities (Jeddah, Rabigh, Yanbu) in Saudi Arabia. The study was used mixed method in data collection. A survey questionnaire was used to collect data from employees and semi-structured interviews were conducted from human resource (HR) managers from several private companies in Saudi Arabia. The employees and managers were selected using convenience sampling. The result showed increased benefits and perks were considered as main retention factor and strategy for both employers, in retaining their employees in company for long period and employees in their intention to stay with their current job. In additions. most important factor was having career plan and appreciation by supervisors. However, lack of qualified candidates and availability of alternative job opportunities made retention challenge in Saudi Arabia. This study recommended managers to develop retention programs and improve current retention practices.